Level of satisfaction and preferences on location and design elements of houses among the disabled community in Kuala Lumpur and Selangor - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Samsudin, Nasriah; Bachok, Syahriah; Rabe, Noor Suzilawati (2017)
By the year 2020, Malaysia aims to be a developed nation with high economic status. In line with that, the housing industry should become adaptive to meet the demand of the people with special needs. The government also needs to plan for suitable housing policies for all groups of people which are sustainable housing policy. House is the central focus for human being including the disabled people and houses that follow housing standard for the disabled will improve their quality of life, thus able to create stability. The location and design of residential property were said to be the most important factor in the selection of property purchase. Location creates desirability, desirability creates demand, and demand raises real estate prices (Ryan, 2016). According to Elizabeth and Julia (2015), the universal home includes thoughtful and well-planned features that make the residence more usable by all family members. This paper aims to study the preferences and level of satisfaction on location and design factor in owning residential property among the disabled community in Kuala Lumpur and Selangor. This study looked at the main preferences of location and designs among the disabled community in owning residential property and the level of satisfaction towards the current location and design’s condition of their residential property. The method used is the quantitative approach where a questionnaires survey were distributed to 800 respondents among the disabled community with mainly focused on two categories of disability, the physical and visual impairment. The outcome of this study will describe the preferences in owning residential property and level of satisfaction among the disabled community on the location and design of their residential property. It concludes by providing housing strategy in planning the location and design of residential property for the disabled community in Kuala Lumpur and Selangor.